In Vitro Hyphal Branching Assay Using Rhizophagus irregularis - Takaya Tominaga; Hironori Kaminaka (Bio-Protocol, 2024)
Most terrestrial plants are associated with symbiotic Glomeromycotina fungi, commonly known as arbuscular mycorrhizal (AM) fungi. AM fungi increase plant biomass in phosphate-depleted conditions by allocating mineral nutrients to the host; therefore, host roots actively exude various specialized metabolites and orchestrate symbiotic partners. The hyphal branching activity induced by strigolactones (SLs), a category of plant hormones, was previously discovered using an in vitro assay system. For this bioassay, AM fungi of the Gigaspora genus (Gigasporaeae) are commonly used due to their linear hyphal elongation and because the simple branching pattern is convenient for microscopic observation. However, many researchers have also used Glomeraceae fungi, such as Rhizophagus species, as the symbiotic partner of host plants, although they often exhibit a complex hyphal branching pattern. Here, we describe a method to produce and quantify the hyphal branches of the popular model AM fungus Rhizophagus irregularis. In this system, R. irregularis spores are sandwiched between gels, and chemicals of interest are diffused from the surface of the gel to the germinating spores. This method enables the positive effect of a synthetic SL on R. irregularis hyphal branching to be reproduced. This method could thus be useful to quantify the physiological effects of synthesized chemicals or plant-derived specialized metabolites on R. irregularis.